The limit of droplet rebound angle - Zhipeng Zhao; Wei Li; Xiaotian Hu; Qiyu Deng; Yiyuan Zhang; Shaojun Jiang; Pengcheng Sun; Hengjia Zhu; Hegeng Li; Siyi Shi; Zhandong Huang; An Li; et al. (Nature Communications)
Abstract Regulating the motion state of droplets after impacting on solid surfaces is crucial in many fields including self-cleaning, energy harvesting, and microfluidics. The rebound angle of the droplet is a key factor in determining its motion state. However, up until now, the limit of droplet rebound angle remains unidentified. Here, we reveal a previously undiscovered droplet rebound behavior that the droplet rolls rapidly along the surface with a rebound angle close to 0 degrees, the limit of the droplet rebound angle. Such unexpected behavior originates from the droplet behaving like two mutually perpendicular springs enabled by continuous asymmetric adhesion provided by the heterogeneous modified nanostructure. This boundary-rolling behavior of droplets contributes to scientific and technical advances in various fields that involve droplet-impact, as illustrated through examples of enhanced cleaning efficiency (improved by 349%) and well-controlled droplet transport in tortuous passages which can hardly be achieved before without external fields coupling.